2014
DOI: 10.1152/ajprenal.00271.2014
|View full text |Cite
|
Sign up to set email alerts
|

Renal cortical hexokinase and pentose phosphate pathway activation through the EGFR/Akt signaling pathway in endotoxin-induced acute kidney injury

Abstract: Smith JA, Stallons LJ, Schnellmann RG. Renal cortical hexokinase and pentose phosphate pathway activation through the EGFR/ Akt signaling pathway in endotoxin-induced acute kidney injury. Am J Physiol Renal Physiol 307: F435-F444, 2014. First published July 2, 2014; doi:10.1152/ajprenal.00271.2014.-While disruption of energy production is an important contributor to renal injury, metabolic alterations in sepsis-induced AKI remain understudied. We assessed changes in renal cortical glycolytic metabolism in a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 72 publications
2
51
0
Order By: Relevance
“…The PI3Ks are a conserved family of signal transduction enzymes that are involved in cellular activation, inflammatory responses, chemotaxis, and proliferation [39,46]. Furthermore, PI3K/Akt have been shown to be downstream components of EGFR activated by different stimuli in various cell types [47,48]. This was confirmed by our observations that thrombin-induced MMP-9 expression and Akt phosphorylation was reduced by the inhibitors of EGFR (AG1478), PI3K (LY294002), and Akt (SH-5), consistent with the results indicating that PI3K/Akt were necessary for angiotensin II-induced MMP-9 expression in breast cancer cells [49].…”
Section: Discussionmentioning
confidence: 99%
“…The PI3Ks are a conserved family of signal transduction enzymes that are involved in cellular activation, inflammatory responses, chemotaxis, and proliferation [39,46]. Furthermore, PI3K/Akt have been shown to be downstream components of EGFR activated by different stimuli in various cell types [47,48]. This was confirmed by our observations that thrombin-induced MMP-9 expression and Akt phosphorylation was reduced by the inhibitors of EGFR (AG1478), PI3K (LY294002), and Akt (SH-5), consistent with the results indicating that PI3K/Akt were necessary for angiotensin II-induced MMP-9 expression in breast cancer cells [49].…”
Section: Discussionmentioning
confidence: 99%
“…EGFR activation is required for renal regeneration and functional recovery after AKI. Smith et al (18) demonstrated that EGF signaling pathway is activated in a mouse model of sepsis-induced AKI. Chen et al (19) reported lower urine EGF levels in infants with severe perinatal asphyxia compared with controls, suggesting that EGF may play a role in the repair of acute renal injury after asphyxia.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have shown that experimental sepsis induces an early anabolic response in renal tissue that is characterized by a shift of metabolism towards aerobic glycolysis 31,32 , followed by a decline in total renal ATP levels 33 . Smith et al showed a significant increase in renal cortical glycolytic metabolism in rodents early after administration of LPS, which was associated with a decline in renal function 31 . In a rodent model of CLP-induced sepsis, we used metabolomic analysis to demonstrate an increase in the levels of glycolytic intermediates concomitant with a decrease in flux through the tricarboxylic acid cycle 32 .…”
Section: The Key Role Of Metabolic Regulationmentioning
confidence: 97%